THE INFLUENCE OF MODERN INNOVATIONS, PANDEMIC AND MILITARY RESTRICTIONS ON THE DEVELOPMENT OF CONVEYANCE ORGANIZATION AND TRANSPORT MANAGEMENT SPECIALISTS’ PROFESSIONAL COMPETENCES - Borets, Oleksii (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to the analysis of the modern innovations and trends influence in the transport industry, as well as pandemic and military restrictions on the development of specialists’ professional competencies in the conveyance organization and transport management. Goals Scientific research encompasses in the theoretical substantiation of the parallel between innovative trends in the development of transport technologies and the state of professional training of specialists in the conveyance organization and transport management in institutions of Ukraine higher technical education. The research is based on theoretical and methodological principles: structural and systemic analysis; systematization, comparison and generalization of information sources, experience and achievements in this area, as well as pedagogical design for modeling the possibilities of applying the obtained results in domestic educational practice. The results. During the conducted research, the main consequences of implementing cutting-edge technological advancements for society as a whole were examined. Emphasis was placed on the necessary changes in the transportation sector, driven by the country's military state. It highlighted the requisite knowledge and skills of professionals in the field of transportation technologies, emphasizing their need to be adaptable and competitive, capable of orchestrating professional activities integrating a wide spectrum of competencies and adapting to the conditions of rapid scientific development. This involves possessing essential professional qualities such as a high level of fundamental and professional knowledge, the ability to actively employ innovations, and skills in profound self-learning. Conclusions. The article identifies the main trends in the development of the transport services market during the pandemic period and establishes the factors of influence, due to the military situation in the country, on the specialist’s professional competencies transformation in the organization of conveyance and transport management in order to increase the requirements for the professional training of industry workers.